Analisis Nilai Moral Dalam Cerita Rakyat Trumon Aceh Selatan - Karmila Yati; Razali Razali; Armia Armia (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
This study entitled "The Analysis of Moral Values in Folklore of Trumon Aceh Selatan. The formulation of the problem is (1) What are the moral values contained in the folklore of Trumon Aceh Selatan, (2. How are the ways of conveying moral values in the folklore of Trumon Aceh Selatan. The purpose of this study is to describe the moral values contained in the folklore of Trumon Aceh Selatan and The method of conveying moral values in the folklore of Trumon Aceh Selatan. The research method used is the qualitative descriptive method. The research data collection technique is obtained through interview techniques, notes, analyzes. Techniques for analyzing the data used in this research are (1) data collection, (2) record the stories obtained from the interviews with the Trumon community regarding the Trumon folklore, (3) Analyzing the results of the stories that have been recorded regarding the Trumon folklore, (4) Analyzing the moral values of the Trumon folklore in South Aceh, (5) Summing up the moral values contained in the Trumon folklore Aceh Selatan. Value mo The things contained in the folklore of Trumon Aceh Selatan are helping, humble, never giving up, willing to sacrifice, gratitude, mutual cooperation, courage, and obedience